Exilic, Becoming Beings (Papers in Arts and Humanities, 2024)
Exile is the unique reliable way out for the world’s citizens when they feel unsafe in their home countries. As such, it is neither confined to any particular era nor to any specific society. This is a pure human phenomenon, which can occur at any time in an individual’s life. Its degree of occurrence might vary, up or down, depending on the political, economic, educational, cultural and legal conditions that a given society offers to its citizens. The more those values are promoted and put into practice, the less the spectrum of exile diminishes. A careful, up-to-date look at the global society helps to remove ambiguities about the exilic people’s conditions. No human society is immune from the exilic phenomenon. Citizens are compelled to leave their native homes to avoid arbitrariness, injustice, and death. As a social fact, exile is considered as a necessary evil. Necessary, because by exiling, the exilic being survives, learns to recreate and reinvent him/herself, overcome social obstacles and negotiate a new way of life. Evil, because the exilic subject, regardless of his/her know-how, intelligence or culture, is perceived as an intruder, a threat to the host community. Thus, the hospitality, which is offered to him/her, is always fraught with difficulties; a dose of adaptation is always required for his/her survival. The issue of exile is recurrent in the 21st century societies and is dealt with in various news media. Literature subjectivizes it by creating fictional, imaginary characters with complex, uncertain exilic destinies. Interrogating the exilic individuals’ conditions through the prism of literary works is therefore an ambitious exercise. For that purpose, Crosian sociocritical perspective will serve as a methodological framework. Its purpose will consist in digging into two major points of interest (exilic evil and integrating modes) in a series of novels by authors of varied nationalities.
Keywords: human; injustice; literature; liminality; exile